1987
DOI: 10.1136/inpract.9.6.196
|View full text |Cite
|
Sign up to set email alerts
|

Air hygiene and equine respiratory disease

Abstract: Air hygiene and equine respiratory disease byAndrew Clarke THE importance of environmental factors on the welfare of the horse have long been appreciated. Percivall (1853) highlighted this point by introducing his treatise on respiratory disease of the horse as follows: 'No general fact appears better established in hippopathology than the one evidencing that disease is the penalty that nature has attached to the domestication of the horse.' Chronic pulmonary disease (CPD) is one such affliction. Clinically CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 2 publications
0
11
1
1
Order By: Relevance
“…The dust content of wood shavings was, however, lower than that of the good quality hay. But like hay or any materials of plant origin, the microflora of straw and wood shavings can change rapidly when a high moisture content is combined with a high temperature (4,7,16,31). These factors may explain the discrepancy between our results and those previously reported by others (4,6,32).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The dust content of wood shavings was, however, lower than that of the good quality hay. But like hay or any materials of plant origin, the microflora of straw and wood shavings can change rapidly when a high moisture content is combined with a high temperature (4,7,16,31). These factors may explain the discrepancy between our results and those previously reported by others (4,6,32).…”
Section: Resultscontrasting
confidence: 57%
“…In summary, the present investigations (1) propose a standardized method for the assessment of the qualitative and quantitative content of dust in different feeds and bedding; (2) demonstrate that alternative materials may be used to decrease airborne dust and aeroallergen in the immediate equine environment and contribute to the improvement of horse management. (4,28,31), but attention needs to be paid to the horse's feed and bedding, which provide the principal sources of dust in stables (31). In addition, around the horse's nostrils, concentrations of respirable airborne dust are significantly greater than levels measured elsewhere in the stall (32).…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of airborne moulds have been identified in equine stables that contain hay and straw , since, if baled with a high moisture content, this herbage is rich in spores of fungi and actinomycetes such as Aspergillus fumigatus, Faenia rectivirgula and Thermoactinomyces vulgaris . In addition to the long‐established observed link between RAO and mouldy hay exposure, several controlled challenge and exposure studies have confirmed this association.…”
Section: Aetiologymentioning
confidence: 85%
“…La utilización de las pesebreras como lugar de almacenamiento de alimento (cuadro 2) no es aconsejable, ya que éste puede atraer roedores que transmiten enfermedades, además el heno en mal estado favorece la presentación de problemas respiratorios como la obstrucción recurrente de las vías aéreas (Clarke 1987, Morán y col 2006.…”
Section: Resultados Y Discusiónunclassified